The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/ast-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Occurrence of Ibuprofen in Sediment, Water, and Biota in River Owena and Ogbese, and its Ecological Risk Assessment

Abstract: AbstractThe volume of pharmaceuticals discharged into the environment increases daily as a consequence of human life. In the present study, the seasonal variation of ibuprofen in sediment, biota, water, and their exposure risk were investigated in River Owena and Ogbese, Nigeria. The high-performance liquid chromatography coupled to a mass spectrometer (HPLC-MS/MS) was used to analyze the samples after clean up and pre-concentration by solid-phase extraction. The mean concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is one of the most consumed drugs in the world and has been found in higher concentration than other analgesics in similar studies in Africa [64,[68][69][70]. Ibuprofen concentration reported in the sediments of Mbokodweni river (9.2 ng/g) and Owena river (2.74 µg/g) was also higher than the concentration in the corresponding water samples [71,72].…”
Section: Analgesicsmentioning
confidence: 80%
“…It is one of the most consumed drugs in the world and has been found in higher concentration than other analgesics in similar studies in Africa [64,[68][69][70]. Ibuprofen concentration reported in the sediments of Mbokodweni river (9.2 ng/g) and Owena river (2.74 µg/g) was also higher than the concentration in the corresponding water samples [71,72].…”
Section: Analgesicsmentioning
confidence: 80%
“…Overall, as far as NSAIDs are concerned, and based on the previously reported studies and others [26][27][28], ibuprofen seems to be one of the most frequently detected NSAIDs in African wastewater. As a consequence, and due to the inefficiency of WWTPs in removing such pharmaceutical drugs, traces of ibuprofen, paracetamol, and other NSAIDs have been detected in African rivers in South Africa and Nairobi River basin in Kenya [29,30].…”
Section: Occurrence Of Cecs In African Wastewater Effluentsmentioning
confidence: 67%
“…IBU is a major drug detected in aquatic ecosystems due to its high consumption and excretion rate (∼70–80 % of the therapeutic dose) [ 11 ]. IBU has been found in surface waters near sewage effluent releases in Nigeria at 0.02–79.45 μg/L and in Brazil, Canada, China, Germany, Italy, Sweden, Britain, and the US at 0.0002–5.04 μg/L [ [13] , [14] , [15] ]. According to Zur et al [ 16 ], IBU was found in receiving waters at a mean concentration of 0.98–67 μg/L in Canada and Greece, 1.0–67 μg/L in Greece, <15–414 μg/L in Korea, and 5.0–280 μg/L in Taiwan.…”
Section: Introductionmentioning
confidence: 99%